PENCIPTAAN DESA PRIMA SADARSIH MELALUI PENINGKATAN PENGETAHUAN PETANI DAN PETERNAK TERHADAP KESADARAN LINGKUNGAN - Nurul Dwi Novikarumsari; Puspaningrum, Diah; Harsita, Pradiptya Ayu; Sri , Subekti; Joni Murti Mulyo , Aji; Widya Widya Kristiyanti , Putri; Susan Barbara , Praticia (PAPUMA: Journal of Community Services, 2025)
Towards a Prima sadarsih Village (Aware of Environmental Cleanliness) was the main program of Turirejo Village in 2025 and supports the Food Security Program initiated by President Prabowo. In line with the Village SDGs, each village is required to realize 18 SDGs for the welfare of the village community. This community service is carried out to support the implementation of SDGs, namely SDGs [2] Hunger-Free Village and SDGs [12] Consumption and Production of Environmentally Conscious Villages. This community service activity is located in Turirejo Village, Jepon District, Blora Regency. Based on data from the Village Development Index, Turirejo Village, Jepon District, Blora Regency is still included in the developing village. One of the main village programs in 2024 focused on food and environmental agriculture problems. These activities aim to increase the environmental awareness of cattle farmers and ranchers in Prima Sadarsih Village. The activity method used is the socialization and extension method. Based on the community service activities carried out, there was an increase of their knowledge from 55% to 90%.